(New) Ecological Problems: Post-pandemic Climate Change Remains an Oceania Existential Threat - David Robie (IKAT: The Indonesian Journal of Southeast Asian Studies, 2021)
Environmental damage, climate change, and increasingly intense natural disasters are serious problems faced by humanity in this millennium. More ecological damage occurs due to expensive and destructive human activities. Illegal logging, expansion of mining areas, pollution of water sources, overfishing, trade-in protected wildlife continue to happen, and the scale is even greater. Meanwhile, climate change is increasingly visible and impacting communities in urban to rural areas. Coastal cities in the United States to coastal villages in the north of Java and the microstates of the South Pacific facing the real impact of sea-level rise. Disasters that occur bring not only material losses but also socio-economic consequences for people affected. The emergence of new ecological problems is being faced by humanity. The complexity of ecological problems is nonlinear, turbulent, and dynamic. This was the theme of the panel (New) Ecological Problems: Defining the Relationship between Humans and the Environment at the Symposium on Social Science 2020. This paper, part of the SOSS 2020 panel on ecological problems, argues for countries to overhaul and “reset” their public health and economic systems to ones based on strengthening multilateral institutions and collaboration, and to abandon or seriously curtail neoliberalism models that have failed. It also argues that the profession of journalism also needs to approach climate change strategies with as much urgency as for addressing the global COVID-19 coronavirus pandemic. The current crisis is a precursor to further crises unless the globe changes its ways to heal both people and the planet.